2018
DOI: 10.1177/0030222818783933
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Awful When We Get It Wrong”: An Exploratory Qualitative Study of Vocational Rehabilitation Counselors’ Perspectives on Suicide

Abstract: Despite the high prevalence of suicide among people with disabilities, little research has explored suicide in the context of the vocational rehabilitation (VR) system. We analyzed the responses of 27 VR counselors who responded to an open-ended qualitative prompt regarding their experiences with suicide training and competency. Key themes included a desire for more training on suicide and the experience of seeking and receiving suicide training and experience outside of VR. Responses also underscored the heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Counsellors' heavy workload leaves them little time for coping with suicidal students. The study also found that counsellors exposed to incidents of suicide had a lower sense of professional self-efficacy (Christianson & Everall, 2008;Lund et al, 2018). Carpenter (2018) pointed out that school counsellors who themselves experienced personal trauma and loss may be even more vulnerable when dealing with adolescents' suicide attempts.…”
mentioning
confidence: 89%
“…Counsellors' heavy workload leaves them little time for coping with suicidal students. The study also found that counsellors exposed to incidents of suicide had a lower sense of professional self-efficacy (Christianson & Everall, 2008;Lund et al, 2018). Carpenter (2018) pointed out that school counsellors who themselves experienced personal trauma and loss may be even more vulnerable when dealing with adolescents' suicide attempts.…”
mentioning
confidence: 89%
“…Client suicidal potential and self‐harming behaviours are a confronting and challenging process that counsellors and psychotherapists will most likely experience more than once in their career (Lund et al, 2020; Wollersheim, 1974). Soon after counselling students embark on their first practicum during their university studies, they will likely be confronted with a client at risk of suicide (Binkley & Leibert, 2015; Mackelprang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand this, one should be equipped with on-line posts on suicide cases especially in social media platforms. Hence the need for more training especially to vocational rehabilitation counselors to enable them tackle the issue of suicide effectively (Lund, Schultz, et al., 2018). Arendt (2018)’s finding that the mass media reports on suicide may have given rise to high incidences of suicide is apt even though it was not tilted to on-line social media platforms.…”
Section: Introductionmentioning
confidence: 99%